Adverse Cardiovascular Events with Nonsteroidal Anti-inflammatory Agents (Rhythmos, 2016)
The extensive use of nonsteroidal anti-inflammatory drugs (NSAIDs), both nonselective and cyclooxygenase- 2–specific inhibitors, for the relief of acute and chronic musculoskeletal pain, in addition to gastrointestinal toxicity, confers serious cardiovascular toxicity that affects the overall risk/benefit ratio of this commonly employed therapy. A plethora of studies have provided convincing evidence for a high risk of adverse cardiovascular events associated with NSAIDs related to a number of risk factors, which are herein briefly reviewed and an algorithm is suggested for their safer use.